Skills Development in the Gauteng - RAMAPEPE, SIMON (My University, 2011)
As part of its broad strategy to tackle rising unemployment, poverty and to facilitate black economic empowerment, the South African government resolved to promote skills development in the workplace. To this end, the national skills development strategy was introduced. This policy came at a time when organisations were battling to increase productivity in the workplace, due to skills shortage. This hampered economic growth and social development in South Africa. The purpose of this research was to examine the implementation of skills programmes for an empowerment company in the Gauteng construction industry. The study used qualitative research methodology. It was established that management showed optimism regarding the implementation of skills plans, whilst workers felt that practical training and financial incentives lacked. It was concluded that skills development is impeded by poor planning and implementation processes. As a result, it was recommended that these be revised and aligned to improve service delivery
MM - P&DM
Keywords: Skills development; Construction industry